Impact of the Timing of Percutaneous Catheter Drainage following Endoscopic Drainage on Outcomes in Acute Necrotizing Pancreatitis - Harsimran Bhatia; Sanya Vermani; Pankaj Gupta; Shameema Farook; Abhishek Kumar; Joseph Johnson; Jimil Shah; Anupam Singh; Vaneet Jearth; Jayanta Samanta; Harshal Mandavdhare; Vishal Sharma; et al. (Indian Journal of Radiology and Imaging, 2024)
Background The role of dual-modality drainage of walled-off necrosis (WON) in patients with acute pancreatitis (AP) is established. However, there are no data on the association of clinical outcomes with the timing of percutaneous catheter drainage (PCD). We investigated the impact of the timing of PCD following endoscopic drainage of WON on clinical outcomes in AP.